Association of Staphylococcus aureus, Streptococcus pyogenes with The Severity of Psoriatic Iraqi Patients in Kerbala Province - Musa, Raaed O.; Abbood, Hayder A. (Scientific Journal of Medical Research, 2022)
Background: Psoriasis is a chronic immune-mediated disorder with cutaneous and systemic manifestations. The presence of a link between certain types of microorganisms and the onset of psoriasis and its worsening had been documented. Aim of the study: The study aimed to study the association of Staphylococcus aureus, Streptococcus pyogenes with psoriasis and disease severity. Method: Across- sectional study was conducted. Thirty-one psoriatic patients have enrolled swabs (lesional skin, non-lesional skin swabs, nasal swabs, and throat swabs). The mean age of the patients was 21.13 ± 13.03. Out of 17 patients were females. The patients were classified according to PSAI score to mild, moderate, and severe cases. The time period for sample collection took about six months in an outpatient clinic, and the samples were examined in an external laboratory. All clinical details of patients were recorded according to the prepared questionnaire. The patients were divided by physician into three groups according to their PASI score: mild (PASI < 10), moderate (PASI 10–29), and severe (PASI > 30). Swab sample: Four swabs were collected from each patient. One from throat, one from nasopharyngeal region, one from skin lesion and one from the non-lesional skin of the patients. Swabs from psoriatic lesions and non-lesional skin were used to determine S. aureus skin colonization. Throat and nasal swabs were used to determine carriage rates of S. pyogenes and S. aureus. The swabs were saved in a transport media until use. Bacterial culturing of the swabs was done on blood agar and pure colony for all bacteria types was prepared to be used in identification. Result: Regarding S. aureus skin colonization, none of the lesional and non-lesional swabs revealed this bacteria’s presence. And concerning throat and nasal carriage of this bacteria, three isolates were recovered from throat swabs (9.67 %) and 4 isolates (12.9 %) from a nasal swab. Psoriatic patients with positive S. aureus growth either in the throat or nasal swabs were fall within mild or moderate PASI. However, there is one person with severe PASI score harbor S. aureus in both nasal and throat swabs. Concerning Sex of psoriatic patients, three bacterial isolates (21.4%) were recovered from nasal swabs collected from male and three throat swab (17.6%) from female, from these, one female has both nasal and throat swabs. All of the recovered isolates from both nasal and throat swabs were collected from patients whom they have the psoriatic lesion for less than 5 years. For Streptococcus pyogenes, none of the throat swabs revealed the presence of this bacteria. In order to explore the presence of previous infection with S. pyogenes, the ASO test was used. The mean level of ASO antibody test was (72.839 ± 66.748) and there was no presence of a significant difference in the mean serum ASO level between mild (66.1 ± 29.09), moderate (75.1 ± 14.15) and severe (78.4 ± 20.59) group of psoriasis (p =>0.715) However, the higher mean was seen in severe cases. Bacterial identification: Colony morphology and culture characteristics was determined on blood agar and mannitol salt agar. Microscopic identification of bacteria was made by using gram staining technique. Biochemical tests was for identifying the isolated bacteria. Confirmation of identification with VITEK 2 compact system. The VITEK 2 automated system (BioMerieux, France) was for the identification of bacterial isolates. Pure culture colonies was used for bacterial identification.